Week-by-week homework for building reading comprehension and fluency - Rose, Mary. (New York : Scholastic, 2004)
Presents a reading comprehension and fluency homework booklet for grades two and three and includes thirty reproducible exercises to enhance reading skills.
"30 reproducible high-interest passages for kids to read aloud at home--with companion actiivities.".
"Grades 2-3.".
Cover title: Week-by-week homework for building reading comprehension & fluency.
Professional
Keywords: Creative activities and seat work; Reading comprehension; Teaching -- Aids and devices; Creative activities; Reading comprehension; Teaching -- Aids and devices